2016
DOI: 10.1002/term.2191
|View full text |Cite
|
Sign up to set email alerts
|

Human platelet lysate supplementation of mesenchymal stromal cell delivery: issues of xenogenicity and species variability

Abstract: Immunogenicity of fetal bovine serum (FBS) poses a problem for its use in the propagation of autologous mesenchymal stromal cells (MSCs) for cell therapy. Human platelet lysate (hPL), an enriched growth factor solution containing mitogenic and angiogenic cues, has potential utility in replacing FBS for human MSC (hMSC) delivery strategies. Despite its potentiation of hMSC number in vitro, little is known concerning its capacity to supplement implanted hMSC-seeded constructs and promote tissue regeneration in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…It also enhanced endothelial cell sprouting alone and in co-culture with MSCs 41 . However, other research found that human PL did not improve cell survival within hydrogel constructs beyond 2 weeks post-implantation 42 . This finding may be explained as being dose dependent as shown in an experiment with MSCs derived from dental pulp.…”
Section: Discussionmentioning
confidence: 90%
“…It also enhanced endothelial cell sprouting alone and in co-culture with MSCs 41 . However, other research found that human PL did not improve cell survival within hydrogel constructs beyond 2 weeks post-implantation 42 . This finding may be explained as being dose dependent as shown in an experiment with MSCs derived from dental pulp.…”
Section: Discussionmentioning
confidence: 90%
“…Platelet lysate is a cocktail of growth factors, anti-inflammatory cytokines, and clot-forming proteins that are involved in tissue repair processes [ 47 , 48 ]. PL is a cost-effective and autologous source of growth factors compared to recombinant growth factors [ 49 ]. Studies suggest that PL significantly increases MSC proliferation compared with fetal bovine serum (FBS) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PL enhances chondrogenic differentiation of MSCs [ 52 ]. However, there are two main drawbacks for PL as scaffold in tissue engineering: a high degradation rate and low mechanical properties [ 49 , 53 ]. Therefore, the mechanical stability of PL-based hydrogels for long-term applications needs to be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, MSCs expanded in PL‐supplemented culture medium exhibited preserved immune‐privileged capacities, such as the suppression of T cell proliferation and activation (Flemming et al, ); such features enabled these cells to be used for treating graft‐vs‐host disease in clinical trials (Introna et al, ). Recently, the utility of human PL to foster cell survival in vivo was also accessed in animal models (Allen, Butts, Copland, Stevens, & Guldberg, ). Although xenogenicity and species variability may affect the preclinical outcome, human‐derived PL has the potential to be applied in important future developments in regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%